Possible horizons for educational innovation in Colombia through contemporary technological perspectives: A training experience with TIC. Contributions of the Project Analysis Model RED-CO CIER Occidente - Ramírez Isaza, Eugenia (Ingeniería Solidaria, 2017)
Introduction: This paper presents an overview of the lecture presented to unesco-unir tic & Education Latam Congress 2016, conducted by unesco and coordinated by Universidad de la Rioja, (unir) in Spain. The lecture was named “Contributions of the Analysis Model as a systematization of project research redco Knowledge Network: cier Occidente” enlightened about the systematization of the final report of the research work that the Education and Virtuality Research Line of the gitt Group (in Terminology and Translation) of Universidad de Antioquia performed between 2014 and 2015 as one of the five universities that participated in the Project of Colciencias cier Occidente, through its Macro Project: redco Knowledge Network. Methodology: This paper begins with an ample view of redco as knowledge network to characterize the core of the research project in question, where redco was endorsed as a pedago- gical methodological matrix based on the appropriation of ict in two EI (Innovative schools) as a basic scenario where multiple paths, channels, and languages coincide, this by a strong technological component. Results and Conclusions: redco cier Occidente promotes teacher training, considering that the chain value in education is teacher centered, as teachers are who program the learning activities, who need to improve the processes, who use new media and share knowledge and good practices to improve the academic services and refine the outcomes.